Planning performance in schizophrenia patients: a meta-analysis of the influence of task difficulty and clinical and sociodemographic variables. Issue 11 (7th April 2017) - Knapp, F.; Viechtbauer, W.; Leonhart, R.; Nitschke, K.; Kaller, C. P.
Abstract : Background: Despite a large body of research on planning performance in adult schizophrenia patients, results of individual studies are equivocal, suggesting either no, moderate or severe planning deficits. This meta-analysis therefore aimed to quantify planning deficits in schizophrenia and to examine potential sources of the heterogeneity seen in the literature. Method: The meta-analysis comprised outcomes of planning accuracy of 1377 schizophrenia patients and 1477 healthy controls from 31 different studies which assessed planning performance using tower tasks such as the Tower of London, the Tower of Hanoi and the Stockings of Cambridge. A meta-regression analysis was applied to assess the influence of potential moderator variables (i.e. sociodemographic and clinical variables as well as task difficulty). Results: The findings indeed demonstrated a planning deficit in schizophrenia patients (mean effect size: $\hat μ \; = 0.67$ ; 95% confidence interval 0.56–0.78) that was moderated by task difficulty in terms of the minimum number of moves required for a solution. The results did not reveal any significant relationship between the extent of planning deficits and sociodemographic or clinical variables. Conclusions: The current results provide first meta-analytic evidence for the commonly assumed impairments of planning performance in schizophrenia. Deficits are more likely to become manifest in problem items with higher demands on planning ahead, which may at least partly explain the heterogeneity of previous findings. As only a small fraction of studies reported coherent information on sample characteristics, future meta-analyses would benefit from more systematic reports on those variables.